ANALYSIS OF ELECTRONIC WORD OF MOUTH, BRAND IMAGE, BRAND TRUST AGAINST PURCHASE INTEREST - Budiarti, Endah (LPPM of NAROTAMA UNIVERSITY, 2024)
This study aims to 1). Analyze and prove the effect of electronic word of mouth on Brand image and Brand trust. 2). Analyze and prove the effect of Brand Image and Brand trust on buying interest. 3). Analyze and prove the effect of electronic word of mouth on buying interest. The population of this research is the University of August 17, 1945 Surabaya students who know the products and brand of Asus laptop. Sampling using a purposive sampling method with the criteria of students who use Asus laptop products and brands. A sample of 190 respondents. The data used in this study are primary data sourced from questionnaires. data analysis and hypothesis testing in this study using the Structural Equation Model (SEM). The results showed that Electronic word of mouth influences brand image variables and Asus Laptop brand trust variables. Brand image and Brand trust affect the variable purchase interest Asus Laptop. Electronic Word of Mouth affects the variable purchase interest Asus Laptop.